2008
DOI: 10.1104/pp.108.124594
|View full text |Cite
|
Sign up to set email alerts
|

Protein Tyrosine Kinases and Protein Tyrosine Phosphatases Are Involved in Abscisic Acid-Dependent Processes in Arabidopsis Seeds and Suspension Cells

Abstract: Protein tyrosine (Tyr) phosphorylation plays a central role in many signaling pathways leading to cell growth and differentiation in animals. Tyr phosphorylated proteins have been detected in higher plants, and the roles of protein Tyr phosphatases and protein Tyr kinases in some physiological responses have been shown. We investigated the involvement of Tyr phosphorylation events in abscisic acid (ABA) signaling using a pharmacological approach. Phenylarsine oxide, a specific inhibitor of protein Tyr phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 83 publications
1
75
0
4
Order By: Relevance
“…MS and MS-MS Analysis-In-gel digests were purified with homemade microcolumns packed with Poros reversed-phase 20 R2 resin (Applied Biosystems) using GELoader tips (Eppendorf) as described previously (13,14). The Poros 20 R2 column was washed with 20 l of 0.1% TFA, and the bound peptides were eluted directly onto the MALDI target using 0.5 l of a matrix solution consisting of ␣-cyano-4-hydroxycinnamic acid (5 mg/ml) in 50% acetonitrile, 0.1% TFA.…”
Section: Left Ventricular Tissue Preparation For Use In Proteomic Andmentioning
confidence: 99%
“…MS and MS-MS Analysis-In-gel digests were purified with homemade microcolumns packed with Poros reversed-phase 20 R2 resin (Applied Biosystems) using GELoader tips (Eppendorf) as described previously (13,14). The Poros 20 R2 column was washed with 20 l of 0.1% TFA, and the bound peptides were eluted directly onto the MALDI target using 0.5 l of a matrix solution consisting of ␣-cyano-4-hydroxycinnamic acid (5 mg/ml) in 50% acetonitrile, 0.1% TFA.…”
Section: Left Ventricular Tissue Preparation For Use In Proteomic Andmentioning
confidence: 99%
“…Maize OBAP1 (LOC 100193701) and Arabidopsis OBAP1a (At1g05510) proteins appeared in proteomic analysis of maize embryos and Arabidopsis seeds, and in both cases, their concentration increased during artificial ageing (Rajjou et al, 2008;Xin et al, 2011). Arabidopsis OBAP1a also appeared in a proteomic analysis focused in the identification of proteins whose Tyr phosphorylation varied significantly in seeds imbibed for 2 d in abscisic acid (Ghelis et al, 2008). These proteomic analysis did not provide any experimental data on the possible subcellular distribution of AtOBAP1a; however, the protein is defined by Ghelis et al (2008) as a "putative lipoprotein."…”
Section: Subcellular Localization Of Obap1 Proteinmentioning
confidence: 99%
“…50 PAO was used to show the implication of PTPs in the ABA-induced expression of RAB16 in barley aleurone cells 51 and of RAB18 expression in A. thaliana suspension cells. 33 The same inhibitor allowed to implicate PTPs in ABAactivated stomatal closure in Arabidopsis. 33,50,52 A PTP activity inhibited by dephostatin has been detected in soybean.…”
Section: Signal Processing By Protein Tyrosine Phosphorylation In Plantsmentioning
confidence: 99%
“…33 The same inhibitor allowed to implicate PTPs in ABAactivated stomatal closure in Arabidopsis. 33,50,52 A PTP activity inhibited by dephostatin has been detected in soybean. 53 Using sodium ortho-vanadate, it has been shown that a PTP is implicated in the copper-dependent transduction pathway leading to cell death 34 and in the dynamics and organization of microtubules.…”
Section: Signal Processing By Protein Tyrosine Phosphorylation In Plantsmentioning
confidence: 99%
See 1 more Smart Citation